(untitled) (Annals of Medical Research, 2022)
Aim: The aim of the current study is to evaluate the epidemiological and demographic characteristics of patients admitted to bonesetters and to determine the complications that occur in these patients. Materials and Methods: Patients who applied to Elazig Fethi Sekin City Hospital due to musculoskeletal trauma between January 2018 and January 2021 and were admitted to a bonesetter before this admission were evaluated retrospectively. The patients’ age, gender, educational status, occupation, reason for applying to the bonesetter, the diagnosis told to the patient by the bonesetter, the actual diagnosis of the patient and the treatment given to the patient were evaluated, respectively. Complications were also evaluated by examining the patient’s physical examination and radiographic examinations. Results: The most common orthopedic disorder in patients was distal radius fracture and the most common reason for utilizing bonesetters was the recommendation of family and relatives. All of the diagnoses made by the bonesetters were defined as dislocations. There was no diagnosis of dislocation among the diagnoses made by physicians. In the student group; joint stiffness was found to be significantly lower than in the worker group. In the worker group; a significantly higher number of deformities were observed. More than half of the patients did not regret applying to a bonesetter. The rate of regret for men to apply to the bonesetters was found to be statistically significantly higher than that of women. Those who answered yes to the question of regret had significantly higher complications than those who answered no. Conclusion: Especially in the eastern regions of our country, the application to bonesetters has been one of the ongoing realities of our country for years. Healthcare professionals have a major role to play in reducing the rate of referrals to bonesetters.